Geographical distribution of Austrolebias monstrosus (Huber, 1995), A. elongatus (Steindachner, 1881) and A. vandenbergi (Huber, 1995) (Teleostei: Cyprinodontiformes), with comments on the biogeography and ecology of rivulidae in pampasic and Chaco floodplains - Alonso, Felipe (2016)
We present a new record for Austrolebias elongatus from Gualeguaychú, in Entre Ríos province, Argentina, based on new fieldwork and a revision of materialdeposited in national ichthyological collections. We also give evidence on the erroneous records of Austrolebias monstrosus and A. vandenbergi from Ituzaingó, Corrientes province, as well as present additional records from Salta province for those species. Material previously determined as A. elongatus from Santiago del Estero is attributed to A. monstrosus. We restrict the distribution of these two species to Semi-arid Chaco Region in Argentina, Paraguay and Bolivia.